Kesejahteraan Emosional sebagai Fondasi Pembentukan Lingkungan Kreatif dan Inklusif bagi Pelajar SMAN 1 Palangka Raya - Nur Asyifa Ananda; Surawan Surawan (Jurnal Cakrawala Pendidikan dan Biologi, 2025)
Emotional well-being is a crucial element in establishing a creative and inclusive learning environment at SMAN 1 Palangka Raya. This study explores the relationship between students' emotional well-being and its impact on creativity and engagement in the learning process. The findings indicate that an environment that supports emotional well-being can reduce anxiety, enhance motivation, and strengthen social interactions between students and teachers. Through an inclusive educational approach, students from diverse backgrounds can actively participate, creating a harmonious and collaborative atmosphere. Emotional well-being not only affects academic performance but also contributes to students' social and emotional development. Therefore, it is essential for schools to integrate strategies that promote emotional well-being into the curriculum and educational policies, thereby creating a better learning environment that supports holistic growth for students at SMAN 1 Palangka Raya.